Investigation of electropolymerized carbon-based nanomaterials as electrodes in energy storage devices for improved microbial fuel cell - Wan Salim, Wan Wardatul Amani; Abd-Wahab, Firdaus; Abd Halim, Amanutazzakiah; Nordin, Anis Nurashikin; Abdul Guthoos, Habibah Farhana; Ismail, Nur Alya Batrisya; Benoudjit, Abdel Mohsen (2020)
Poly (3,4-ethylenedioxythiophene) poly (sodium 4-styrenesulfonate) (PEDOT:PSS) electropolymerized and deposited onto screen-printed carbon electrodes (SPCEs) was studied for anodic/cathodic peak current and cycle stability (life cycle). Cyclic voltammetry (CV) shows that the redox ability of SPCEs electropolymerized with PEDOT:PSS (SPCE/PEDOT:PSS) was significantly improved (ΔISPCE = 350 μA). Oxidation and reduction peak current of the CVs showed that the modified electrode could maintain electrode integrity for over 30 days. The results suggest that the electropolymerized PEDOT:PSS had good adhesion to SPCE surfaces. There was an insignificant change in the life cycle curve after 3000 cycles compare to the initial cycle and an insignificant change in the life cycle after 30 days in comparison to the first day. The results suggest that electrode integrity of SPCE/PEDOT:PSS was maintained after repetitive CV cycles in aqueous media, which could be applied as electrodes in microbial fuel cells and energy storage devices like a battery, capacitor, and supercapacitor.